Guide wire electrode versus liquid electrode for intravascular electrocardiography–guided central venous catheterization in adults: A systematic review and meta-analysis. Issue 5 (September 2020) - Ling, Guo; Zhiwen, Wang; Guorong, Wang; Shaomei, Shang; Xue, Wu
Aim: To assess the effectiveness and safety of guide wire electrode versus liquid electrode for intravascular electrocardiography–guided central venous catheter placement in adults. Design: Systematic review and meta-analysis. Data sources: We searched the main electronic databases (Cochrane Library, the Joanna Briggs Institute Library, Embase, PubMed, CINAHL, China National Knowledge Infrastructure, and Wanfang) with articles published from inception up to March 2018. References of important articles were also screened for relevant studies. We used a structured search strategy and did not apply any search limitations. Review methods: Randomized, controlled trials, quasi-experimental studies or studies using a within-subject design, evaluating guide wire electrode versus liquid electrode for intravascular electrocardiography–guided central venous catheter placement in adults, were eligible for inclusion. Risk of bias assessment was performed using the Cochrane Collaboration's tool and meta-analysis was performed using RevMan 5.3. Results: In total, six studies with a total of 2176 participants were included. Meta-analysis showed that there was no statistically significant difference in accuracy of tip location placement between guide wire and liquid electrodes. Use of guide wire electrode had a higher risk of complications which were transient and there were an insufficient number of studies using the same parameters to evaluate intravascular electrocardiography signal quality. Conclusion: Due to the small number and low quality of identified studies, it is difficult to draw definitive conclusions on the relative effectiveness and safety of guide wire versus liquid electrodes for the placement of central venous catheters in adults. More well-designed studies are needed in the future.